2017
DOI: 10.1021/acs.macromol.7b00357
|View full text |Cite
|
Sign up to set email alerts
|

SANS Evidence of Liquid–Liquid Phase Separation Leading to Inversion of Crystallization Rate of Broadly Distributed Random Ethylene Copolymers

Abstract: Aiming to understand the inversion of crystallization kinetics observed by DSC, detailed SANS investigations of the melt structure of a broadly distributed ethylene–1-hexene copolymer have been undertaken in a wide range of temperatures that were reached either by heating the solid or cooling from the homogeneous melt state. In both cases, the observed SANS signal transitions from a scattering cross section consistent with a homogeneous melt state (high temperature range) to an intensity that in the low Q regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 49 publications
2
19
0
Order By: Relevance
“…Additionally, after complete melting of polymeric crystals, some memory of the crystalline ordered structure can still survive, and the crystallization of the polymer can be enhanced by melt memory effects. [6][7][8][9][10][11] Polybutene-1 is a polyolefin with excellent mechanical properties and complex polymorphic behavior that has attracted much interest from both industry and academia. 12,13 The tetragonal Form II with an 11/3 helix can be obtained by cooling the sample directly from the melt.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, after complete melting of polymeric crystals, some memory of the crystalline ordered structure can still survive, and the crystallization of the polymer can be enhanced by melt memory effects. [6][7][8][9][10][11] Polybutene-1 is a polyolefin with excellent mechanical properties and complex polymorphic behavior that has attracted much interest from both industry and academia. 12,13 The tetragonal Form II with an 11/3 helix can be obtained by cooling the sample directly from the melt.…”
Section: Introductionmentioning
confidence: 99%
“…Comparing with the homopolymer PB‐1, which possesses a narrow Domain II , it is noticeable that self‐nuclei of P(B1‐ran‐E) can survive even above the equilibrium melting temperature of PB‐1 homopolymer (148°C), 46 alike other polyethylene copolymers 15,16,29 . In particular, based on the definition proposed by Müller et al, 7,17,26 Domain II could be divided into Domain IIa , if the heat flow signal reaches the baseline (indicating all crystals have melted), and Domain IIb , if the signal is still within the melting endotherm (indicating that a small crystal population or crystal fragments remain that can act as self‐seeds).…”
Section: Resultsmentioning
confidence: 99%
“…Alamo et al 15,16,29 observed an unexpected strong melt memory effect in polyethylene copolymers above the equilibrium melting temperature. They interpreted the mechanism behind this peculiar phenomenon as the formation of a complex topology of knots, loops, ties, and other entanglements within the inter‐crystalline regions, which are caused by the selection and dragging process of polymer chains when suitable ethylene sequences with low branch contents are packed into the lattice.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…For examples, Knauer et al labeled the chain ends of polyethersulfone (PESU), to locate the accurate position of chain ends in PESU thin film‐air interface . Chen et al investigated the mechanism of liquid–liquid phase separation in random ethylene 1‐hexene copolymer by adding deuterium to certain fractions . Deuterated polyethylene (PE) was proved to be the key in elucidating the shish‐kebab superstructures and chain alignment of PE under cold‐draw through small‐angle neutron scattering (SANS) .…”
Section: Introductionmentioning
confidence: 99%